The Sharia Inquiry, Religious Practice and Muslim Family Law in Britain: Book Review - Nabila Aulia Syifa (Journal of Islamic Studies and Education, 2024)
Simo Bano’s The Sharia Inquiry, Religious Practice, and Muslim Family Law in Britain provides a comprehensive and thought-provoking analysis of the intersection between religious practice, legal pluralism, and family law within the British Muslim community. The book examines how Sharia councils, religious marriage practices, and British legal frameworks interact, particularly in the areas of marriage, divorce, and gender rights. Bano critically engages with the 2016 Sharia Inquiry initiated by then-Prime Minister Theresa May, led by Professor Mona Siddiqui, which investigated the misuse of Sharia law and its compatibility with domestic law in England and Wales.